Development and validation of the Fitness Coaching Behavior Scale: Factor structure, validity and reliability (Desarrollo y validación de la Escala de Comportamiento del Instructor de Fitness: Estructura factorial, validez y fiabilidad) (Desenvolvimento e - Rodrigues Sampaio, António Carlos; Pimenta, Nuno; Machado, Mafalda; Teques, Pedro (Retos, 2020)
Abstract. The purpose of the present research was to develop and provide initial validation of the Fitness Coaching Behavior Scale (FCBS-Fit) designed for assessing perceived the quality of instructor’s behaviors in fitness group classes through the theoretical adaptation to the Coaching Model (Côté et al., 1995), originally derived from sports. In total, 618 participants of fitness group classes accepted to participate in this investigation. The purpose of the research was achieved in three phases: (1) development of the item pool and content validation of the preliminary version of the FCBS-Fit (27 items); preliminary examination of the factorial structure through exploratory factor analysis (n1 = 185) that revealed a scale with 20 items distributed by 4 factors: Technical and Positive Rapport, Exercise Planning and Prescription, Negative Rapport, and Goal Setting; (2) confirmatory factor analysis to the 4-factor model indicated adequate fit model fit, reliability and convergent and discriminant validity. In addition, a multi-group CFA indicated measurement invariance of the factorial structure across samples (n2 = 210); (3) structural equation model examined criterion validity through analysis of the relationships between the 4-factors of EPCI-Fit and enjoyment in exercise (n3 = 223). Psychometric evidence suggests that the FCBS could be used as a reliable and valid measure to assess Portuguese participant`s perceptions of the quality of instructor’s behaviors in fitness group classes. Resumen. El propósito del presente estudio fue desarrollar y validar preliminarmente la Escala de Percepción del Comportamiento del Instructor de Fitness (EPCI-Fit) cuyo objetivo es evaluar la calidad de los comportamientos de los instructores de fitness en clases de grupo, a través de la adaptación teórica al Coaching Model (Côté et al., 1995), original del entrenamiento deportivo. En total, participaran 618 practicantes de fitness en clases de grupo de diversas áreas del litoral de Portugal continental. El propósito del estudio fue alcanzado en tres fases: (1) desarrollo del banco de ítems y validación inicial del contenido de la versión inicial de EPCI-Fit (27 ítems); la evaluación preliminar de la estructura factorial a través de análisis factorial exploratorio (n1 = 185) que resultó en una escala con 20 ítems distribuidos por 4 factores - Feedback técnico positivo, Feedback negativo, Formulación de objetivos, y Planificación y prescripción del ejercicio; (2) estimación del ajuste del modelo de 4-factores a través de análisis factorial confirmatorio, y análisis a la fiabilidad compuesta, y validez convergente y discriminante (n2 = 210); evaluación de la invariancia métrica del modelo de 4-factores en dos muestras independientes (n1 = 185; n2 = 210); y (3) estimación de la validez de criterio a través del análisis a las relaciones entre los 4-factores de la EPCI-Fit y el disfrute en la práctica de ejercicio (n3 = 223). En general, los resultados provenientes de las diferentes fases de análisis psicométrico a EPCI-Fit soportan la validez y la fiabilidad de los datos, indicando que esta escala podrá ser utilizada en el futuro para evaluar las percepciones de la calidad del comportamiento del instructor de fitness en clases de grupo. Resumo. O propósito do presente estudo foi desenvolver e validar preliminarmente a Escala de Perceção do Comportamento do Instrutor de Fitness (EPCI-Fit) cujo objetivo é avaliar a qualidade dos comportamentos dos instrutores de fitness em aulas de grupo, através da adaptação teórica ao Coaching Model (Côté et al., 1995), original do treino desportivo. No total, participaram 618 praticantes de fitness em aulas de grupo de várias zonas de Portugal continental. O propósito do estudo foi alcançado em três fases: (1) desenvolvimento da pool de itens e validação inicial do conteúdo da versão inicial da EPCI-Fit (27 itens); avaliação preliminar da estrutura fatorial através de análise fatorial exploratória (n1 = 185) que resultou numa escala com 20 itens distribuídos por 4 fatores – Feedback técnico positivo, Feedback negativo, Formulação de objetivos, e Planificação e prescrição do exercício; (2) estimação do ajustamento do modelo de 4-fatores através de analise fatorial confirmatória, e análise à fiabilidade compósita, e validade convergente e discriminante (n2 = 210); avaliação da invariância métrica do modelo de 4-fatores em duas amostras independentes (n1 = 185; n2 = 210); e (3) examinação da validade de critério através da análise às relações entre os 4-fatores da EPCI-Fit e o divertimento na prática de exercício (n3 = 223). No geral, os resultados oriundos das diferentes fases de análise psicométrica à EPCI-Fit suportam a validade e a fiabilidade dos dados, indicando que esta escala poderá ser utilizada futuramente para avaliar as perceções da qualidade do comportamento do instrutor de fitness em aulas de grupo.